Mediävistik und Schadensrecht Gedenkfeier anlässlich des hundertsten Geburtstages von Hermann Lange (1922-2018) - Schiemann, Gottfried (Mohr Siebeck, 2023)
To mark the centenary of his birth, colleagues pay tribute to the legal scholar Hermann Lange by taking stock of medieval Romance studies, a field which is still decisively influenced by Langes monumental work Römisches Recht im Mittelalter.
PublicationDate: 20230926
Keywords: Römisches Recht -- Mittelalter -- Gedenkfeier Hermann Lange -- Optimismus -- Wissenschaftsgeschichte -- Rechtsgeschichte -- Bürgerliches Recht